ANALISIS KETERAMPILAN KOMUNIKASI LISAN SISWA DALAM PEMBELAJARAN IPS: Penelitian Survey di Sekolah Dasar di Kecamatan Paprongpong, Kabupaten Bandung Barat - Riskita Hoerunnisa, - (2020)
Seiring dengan berkembangnya ilmu pengetahuan teknologi, siswa dituntut untuk memiliki kompetensi salah satunya keterampilan komunikasi lisan, keterampilan berkomunikasi lisan merupakan salah satu keterampilan di pendidikan abad ke-21. Di dalam proses pembelajaran keterampilan komunikasi menuntut adanya komunikasi guru dan siswa ataupun siswa dengan siswa lainnya. Komunikasi menjadi penting karena bisa menjadi modal khususnya dalam pembelajaran, salah satu mata pelajaran yang dapat mengantarkan komunikasi lisan yaitu pembelajaran IPS. Maka penelitian ini bertujuan untuk mengetahui bagaimana keterampilan komunikasi lisan siswa di sekolah dasar, faktor-faktor yang mempengaruhi keterampilan komunikasi lisan dan bagaimana ideal keterampilan komunikasi lisan di sekolah dasar. Penelitian ini dilaksanakan berlandaskan pada komunikasi lisan yang dipengaruhi oleh faktor pembelajaran IPS. Penelitian ini menggunakan metode survey dan sumber data yang diperoleh dari jawaban responden dan hasil wawancara guru, instrumen yang digunakan dalam penelitian ini adalah kuesioner dan wawancara. Hasil penelitian ini dari jawaban responden bahwa keterampilan komunikasi lisan siswa menunjukkan kategori interval "Baik" di dalam pembelajaran. baik atau buruknya keterampilan komunikasi ini bukan hanya dari siswa yang belajar IPS saja, namun terdapat faktor-faktor lain seperti pengetahuan, persepsi, lingkungan dan hubungan. ----- Along with the development of technological knowledge, students are required to have competencies, one of which is oral communication skills, oral communication skills are one of the skills in 21st century education. In the learning process, communication skills require communication between teachers and students or students with other students. Communication is important because it can be an asset, especially in learning, one of the subjects that can deliver oral communication, namely social studies learning. So this study aims to determine how the oral communication skills of students in elementary schools, the factors that affect oral communication skills and how ideal oral communication skills in elementary schools. This research was conducted based on oral communication which was influenced by social studies learning factors. This study used a survey method and data sources obtained from respondents' answers and the results of teacher interviews. The instruments used in this study were questionnaires and interviews. The results of this study from the respondents 'answers that the students' oral communication skills showed the interval category "Good" in learning. Good or bad communication skills are not only from students who study social studies, but there are other factors such as knowledge, perception, environment and relationships. The instruments used in this study were questionnaires and interviews. The results of this study from the respondents 'answers that the students' oral communication skills showed the interval category "Good" in learning. Good or bad communication skills are not only from students who study social studies, but there are other factors such as knowledge, perception, environment and relationships. The instruments used in this study were questionnaires and interviews. The results of this study from the respondents 'answers that the students' oral communication skills showed the interval category "Good" in learning. Good or bad communication skills are not only from students who study social studies, but there are other factors such as knowledge, perception, environment and relationships.